INFLUENCE OF THE OVERLAP COEFFICIENT ON THE CONTRAST IN LASER MARKING OF C110W STEEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The laser marking process by melting samples of C110W carbon tool steel was studied. The experiments were performed with a fiber laser and a CuBr laser. A field of squares is marked in a raster method for different values of the overlap coefficient and power density. The contrast of the marking is determined on each marked square. From the obtained experimental data, graphs of the dependence of the contrast on the overlap coefficient for three power densities were drawn. The obtained results for the two lasers are compared and the influence of the wavelength is indirectly analysed. The working intervals of the overlap coefficient for the studied power densities for the two lasers at which the optimal contrast in the processing zone is obtained are determined.